2023
DOI: 10.1101/2023.03.13.532485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular mechanisms of catalytic inhibition for active site mutations in glucose-6-phosphatase catalytic subunit 1 linked to glycogen storage disease

Abstract: Mediating the terminal reaction of gluconeogenesis and glycogenolysis, the integral membrane protein G6PC1 regulates hepatic glucose production by catalyzing hydrolysis of glucose-6-phosphate within the lumen of the endoplasmic reticulum. Because G6PC1 function is essential for blood glucose homeostasis, inactivating mutations cause glycogen storage disease (GSD) type 1a, which is characterized by severe hypoglycemia. Despite its physiological importance, the structural basis of G6P binding to G6PC1 and the mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…The benefit of additional charged residues in the substrate cavity may also explain why individual mutation of residues 36 and 252, which would break the predicted ionic interaction and make another charged residue available for interacting with the substrate, increase the G6Pase activity of G6PC2 whereas mutation of both residues does not ( Figure 4 ). Alternatively, studies in G6PC1 have suggested that D254, the residue corresponding to D252 in G6PC2, may directly interact with G6P during hydrolysis and support the formation of a substrate bound state [ 61 ]. By promoting a potential ionic interaction between residues 36 and 308 in G6PC2, this may allow D252 to interact with the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of additional charged residues in the substrate cavity may also explain why individual mutation of residues 36 and 252, which would break the predicted ionic interaction and make another charged residue available for interacting with the substrate, increase the G6Pase activity of G6PC2 whereas mutation of both residues does not ( Figure 4 ). Alternatively, studies in G6PC1 have suggested that D254, the residue corresponding to D252 in G6PC2, may directly interact with G6P during hydrolysis and support the formation of a substrate bound state [ 61 ]. By promoting a potential ionic interaction between residues 36 and 308 in G6PC2, this may allow D252 to interact with the substrate.…”
Section: Discussionmentioning
confidence: 99%